Update on the Therapies of Severe Lupus Nephritis - Mok, Chi C. (Current Rheumatology Reviews, 2006)
Therapy of lupus nephritis should target at symptomatic control, preservation of renal function, reduction of renal flares, prevention of complications and treatment-related toxicities. Despite the emergence of newer modalities, cyclophosphamide (CYC) remains the most commonly prescribed therapy. This is because of the considerable experience with this agent and the availability of long-term data beyond 10 years. Modification of CYC-containing regimens or early substitution with a less toxic immunosuppressive agent in good responders may help to reduce toxicities. Alternative induction regimens using newer agents such as mycophenolate mofetil (MMF) and the calcineurin inhibitors may also be considered in selected patients without poor prognostic factors. Recalcitrant lupus nephritis carries a high risk of renal function deterioration. Newer and more aggressive therapies, including experimental agents, such as immunoablative CYC, immunoadsorption and the biological response modifiers may be considered on an individual basis.
Keywords: lupus erythematosus